Tinjauan Yuridis Hukum Administrasi Negara terhadap Pengadaan Tanah bagi Kepentingan Umum berdasarkan Peraturan Pemerintah Nomor 19 Tahun 2021 - Anggian, Dolly; Atmei Lubis, Anggreni; Adi Syaputra, M. Yusrizal (Universitas Medan Area, 2024)
Land Acquisition for the Public Interest aims to provide land for the implementation of development to improve the welfare and prosperity of the nation, state and society while still guaranteeing the legal interests of the Eligible Parties. Based on Government Regulation Number 19 of 2021, the research method used is normative juridical with an approach through literature study and analyzed qualitatively. This study concludes that land banks have a strategic role as a national land management tool, especially in terms of land tenure and management, so as to realize greater prosperity for the people. This is also reinforced by the fact that land bank activities have been successfully implemented in various developed countries to systematically overcome various land problems, for example, land that has been developed, abandoned land or vacant land and land that is considered abandoned, as well as land that is considered occupied. potential growth to be more efficient. That there are 3 (three) basic values of law, called legal ideals, where the law must fulfill these basic values, namely: justice, expediency (zweckmaszigkeit) and legal certainty. As a basic value that must be respected, the instrument for regulating land reserves in the future must be able to take into account the achievement of these three basic values.